2018
DOI: 10.1590/1808-1657000022017
|View full text |Cite
|
Sign up to set email alerts
|

Soybean yield loss and economic thresholds due to glyphosate resistant hairy fleabane interference

Abstract: The interference of glyphosate resistant hairy fleabane (Conyza bonariensis) has caused yield losses in soybean crop. Knowledge of the economic threshold is an important aspect for the economic management of resistant weeds. Because of it, the interference of the glyphosate resistant hairy fleabane density on the soybean yield loss was evaluated, as well as to estimate the economic threshold. Two experiments were conducted to verify the effect of different weed densities on the yield of two soybean cultivars (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…In the same way, Agostinetto et al (2017) who reported that the soybean planting interfered with hairy fleabane infestation showed the loss of growth and yield against soybean is more harmful than the soybean planting alone (no weed interference).…”
Section: The Effects Of Different Density Of Four Weed Species Interfered With Soybean Planting On Growth Performance Against Soybeanmentioning
confidence: 78%
See 1 more Smart Citation
“…In the same way, Agostinetto et al (2017) who reported that the soybean planting interfered with hairy fleabane infestation showed the loss of growth and yield against soybean is more harmful than the soybean planting alone (no weed interference).…”
Section: The Effects Of Different Density Of Four Weed Species Interfered With Soybean Planting On Growth Performance Against Soybeanmentioning
confidence: 78%
“…The accumulation of the weed density in crop planting showed the growth retardation as well as the minimization of yield is more harmful than the reduction of the weed density (Agostinetto et al, 2017). For the soybean planting and economic field crops interfered with weeds competition showed the injury of some characters of crops and soybean planting included reduction of the growth characters (Keramati et al, 2008), damage of the yield components (Du et al, 2019) and decrease of the yields (Korres et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent estimates, more than 10 million ha cultivated with soybean are currently infested with herbicide resistant Conyza populations in Brazil (Adegas et al 2017). Considering that Conyza interference can cause up to 91% yield loss (Agostinetto et al 2017), effective management strategies must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Hairy fleabane [Conyza bonariensis (L.) Cronquist] is a weed of the Asteraceae family whose main characteristics are high competitivity and prolificacy, producing more than 800 thousand seed per plant (Kaspary et al, 2017). Worldwide, hairy fleabane is one of the main weeds in wheat, soybean, and maize cultivations, causing significant drops of grain yield (Vargas et al, 2007;Agostinetto et al, 2017). Furthermore, there are recognized cases of this species resistance to several mechanisms of herbicidal action, the main of which is the resistance to glyphosate (Heap, 2019).…”
Section: Introductionmentioning
confidence: 99%